A Novel Broadband Printed Dipole Antenna and Its Application for TD-LTE Communications. (3rd September 2014) - Wang, Can; Ge, Yuehe
Abstract : Novel double-sided printed dipole antennas are proposed and investigated in this paper. Two pairs of identical T-shape metallic loadings are connected to the traditional double-sided printed dipole, enhancing the operating bandwidth. Simulations show that the proposed printed dipole without the reflecting ground plane gives a bandwidth of up to 90.7% for S 11 < - 10 dB or 84.9% for S 11 < - 15 dB, which is significantly greater than those of the traditional printed dipole. The proposed dipole is then applied to design a dual-polarized printed dipole antenna, mounted on a ground plane. Measurements for the prototype show a bandwidth of 68.8% for S 11 < - 10 dB, covering the entire TD-LTE band. The gain is about 6–8 dBi and the isolation is over 24 dB over the bandwidth.